Une université privée égyptienne dans le nouveau marché international de l'enseignement supérieur - Daniele Cantini (Les éditions de la Maison des sciences de l'Homme, 2014)
As it is the case with migration proper, also when dealing with university students' movements Egypt represents both sides of the medal - at one time point of departure for many, especially to the USA and different European states, and a receiving country. This paper focuses on the "new" Egyptian private universities, for-profit institutions established since 1996 and that are now mushrooming all over the country, and particularly on the biggest of them, the University of 6th of October (O6U), on which I carried out ethnographic research in 2010 and 2012. This paper helps to apprehend, through the case of the new private universities, the importance of South-South student mobility during the last fifteen years in Egypt, keeping an eye on the ongoing policies of higher education reform in the country.